The extent to which TQM standards can be applied in the judiciary institution (Iraq as a model - محمد, عبد الباسط جاسم (Journal of Legal Sciences, 2020)
The use of the concept of (quality), which is purely administrative, and part of the system of competitive activity (private), within the framework (judicial) (public), in a manner that helps achieve the strategic objective of the judiciary, which is to maintain its leading position among the means of dispute settlement, with Upgrading (products) of judgments and fatwas, in order to achieve excellence in its performance, and to ensure the satisfaction of (adversaries) when they resort to him, and not to look for other alternatives, which helps the judicial institution (public) to improve in the provision of (services), and this is achieved by benefiting from The advantages offered by TQM in its concept (private institutions).